Outcome of pulmonary embolism with and without ischemic stroke - Keller, Karsten; Schmitt, Volker H.; Hahad, Omar; Hobohm, Lukas (Journal of Clinical Medicine, 2024)
Background: Ischemic stroke is the second, and pulmonary embolism (PE) is the third most common cardiovascular cause of death after myocardial infarction. Data regarding risk factors for ischemic stroke in patients with acute PE are limited. Methods: Patients were selected by screening the German nationwide in-patient sample for PE (ICD-code I26) and were stratified by ischemic stroke (ICD code I63) and compared. Results: The nationwide in-patient sample comprised 346,586 hospitalized PE patients (53.3% females) in Germany from 2011 to 2014; among these, 6704 (1.9%) patients had additionally an ischemic stroke. PE patients with ischemic stroke had a higher in-hospital mortality rate than those without (28.9% vs. 14.5%, p < 0.001). Ischemic stroke was independently associated with in-hospital death (OR 2.424, 95%CI 2.278-2.579, p < 0.001). Deep venous thrombosis and/or thrombophlebitis (DVT) combined with heart septal defect (OR 24.714 [95%CI 20.693-29.517], p < 0.001) as well as atrial fibrillation/flutter (OR 2.060 [95%CI 1.943-2.183], p < 0.001) were independent risk factors for stroke in PE patients. Systemic thrombolysis was associated with a better survival in PE patients with ischemic thrombolysis who underwent cardio-pulmonary resuscitation (CPR, OR 0.55 [95%CI 0.36-0.84], p = 0.006). Conclusions: Ischemic stroke did negatively affect the survival of PE. Combination of DVT and heart septal defect and atrial fibrillation/flutter were strong and independent risk factors for ischemic stroke in PE patients. In PE patients with ischemic stroke, who had to underwent CPR, systemic thrombolysis was associated with improved survival.
Gesehen am 06.09.2024